Quantitative Assessment of the Medicinal Flora of Gadoon valley, District Swabi, Khyber Pakhtunkhwa, Pakistan - Ullah, Fazal; Irfan, Muhammad; Khan, Kamran; Khatoon, Shazia; Khalil, Saeed; Zubair, Muhammad; Zainab, Rimsha; Saeed, Muhammad; Sher, Ali (Ethnobotany Research and Applications, 2024)
Background: This study explores the folk medicinal knowledge of Gadoon Valley, District Swabi, Khyber Pakhtunkhwa, Pakistan, focusing on the diversity of medicinal plants and their uses for various human health issues. The information was collected through field assessments to document the local ethnobotanical practices. Methods: Regular ethnobotanical surveys were conducted from November 2022 to 2023. The objective was to gather and document ethnobotanical knowledge from local residents and farmers. Participants were briefed that the survey was solely for research purposes, ensuring their willingness to share authentic information. Results: The study illustrates 60 plant species consists of 28 families. Among these, one family belonged to the Gymnosperm division with two species, while the rest were Angiosperms. The most dominant family was Fabaceae with six species (10%), followed by Lamiaceae with five species (8.33%), and Asteraceae, Brassicaceae, and Cucurbitaceae each with four species (20%). Herbs were the most common habit with 34 species, followed by trees with 17 species. Leaves were the most commonly used plant part (21 species), followed by whole plants (20 species). The use value (UV) of ethnomedicinal taxa ranged from 1.24 to 0.06, with the highest UV for Foeniculum vulgare (1.24). The relative frequency of citation (RFC) ranged from 1.99 to 0.01, highest for Morus alba (1.99). Fidelity level (FL) values ranged from 1.980 to 0.09, with the highest for Pinus roxburghii (1.980). Relative preference level (RPL) values ranged from 1.96 to 0.5, highest for Convolvulus arvensis and Daucus carota (1.96). Relative popularity (ROP) values ranged from 1.97 to 0.15, highest for Prunus domestica and Taraxacum officinale (1.97). However, among the treated disease the bronchitis was the most commonly treated disease (0.969). Conclusions: The findings indicate that Gadoon Valley is rich in floristic diversity. However, the medicinal plant resources are threatened by flooding, unsuitable agricultural practices, overgrazing, overexploitation, and deforestation for fuel and timber. Keywords: Ethnobotany; Gadoon valley, Swabi, Khyber Pakhtunkhwa, Pakistan